PENGARUH PEMBERIAN AMPAS TEH TERHADAP PERTUMBUHAN TINGGI TANAMAN HIAS SRI REJEKI (AGLAONEMA ROYAL RIPPLE ) - Halisah Suriani (KOLONI, 2023)
This study aims to determine the effect of giving tea dregs on the growth of the ornamental plant Sri Rejeki (Aglaonema royal ripple). This research was conducted at the laboratory of the Faculty of Teaching and Education, Gunung Leuser University, Aceh on January 4-31 2023. The design used in this study was a completely randomized design (CRD) with 5 (five) treatments and 3 (three) replicate treatments so that the total there are 15 trials. The parameters observed in this study were plant height which was seen from the age of 7 hst, 14 hst, 21 hst, 28 hst. The result showed that use of te dregs had a significant effect on the growth of Sri Rejeki (Aglaonema royal ripple) ornamental plants on plant height parameters in the first week F count (35,87) < F table significant level (5%) and (1%), at second week F count (10,08) < F table significant level (5%) and (1%), third week F count (64,45) > F table significant level (5%) and (1%), at fourth wek F count (106,31) > F table (5%) and (1%). Keywords: tea dregs, Ornamental Plants, Aglaonema royal ripple